Antibiotic Use in Digestive Surgery Patients with the Anatomical Therapeutic Chemical-Defined Daily Dose Method - Sahat Saragi; Agnes Stefania Martirini (Jurnal FARMASIMED (JFM), 2025)
Background: The use of antibiotics serves as therapy for various types of infections caused by pathogens or for other preventive measures, such as major surgeries. Evaluating antibiotic use is necessary to ensure effectiveness, accuracy, and safety in rational usage. Purpose: The aim of this study was to evaluate the use of antibiotics at dr. T.C. Hillers Maumere General Hospital in 2019 among inpatients undergoing digestive surgery. Method: This research is a descriptive, non-experimental study with a cross-sectional design. A quantitative and qualitative approach was used, employing the Anatomical Therapeutic Chemical/Defined Daily Dose (ATC/DDD) method and the Gyssens flowchart based on retrospective data. The study involved reviewing medical records from January to December 2019. A total of 338 data samples were collected, including 9 types of oral antibiotics and 8 types of parenteral antibiotics according to the ATC classification. Results: The results showed that among oral antibiotics, Cefadroxil 500 mg had the highest DDD value at 9.51 DDD/100, while among parenteral antibiotics, Cefotaxime 1 g injection had the highest DDD value at 10.74 DDD/100. Conclution: The evaluation using the Gyssens flowchart indicated that 68.34% of antibiotic use was appropriate, while 31.66% was inappropriate. In conclusion, the use of antibiotics for digestive surgery inpatients was generally appropriate, but further evaluation is needed regarding antibiotic use that does not comply with clinical guidelines.